The British Liberal Party and the Liquor Licensing Question, 1895-1905 - Wright, Edwin David (My University, 1972)
This work attempts first to explain why by 1895 liquor licensing was regarded as a major political issue in Britain. The nature and extent of contemporary concern with the drink problem is analyzed, followed by a brief discussion of how the two major parties had polarized on the licensing issue by 1895, with the Conservatives being regarded as the party of the licensed trade interest and the Liberals the party of the temperance movement.
Then this work examines the Liberal Party's attitude! to the licensing question between 1895 and 1905. The decisive defeat of the party in 1895 was followed by a reassessment of the party's policies and purposes. The Liberal commitment to a semi-prohibitionist platform was held by many to have been a major cause of the defeat. Late in 1897 there began a campaign, led by Herbert Gladstone, to free the party from this commitment A Royal Commission on the liquor licensing laws reported in 1899. Under the guise of adopting the Commission's Mnority Report, Herbert Gladstone and the Liberal leadership laboriously constructed for their party a far more flexible licensing policy. Despite protests from important sections of the temperance movement, they managed to hold to the new policy until 1906 and the great Liberal election victory of that year.
Among the material consulted were manuscript collections, contemporary works on the drink problem and the licensing question, and the evidence presented before the 1896-99 Royal Commission on the Llquor Licensing Laws.
Keywords: History; History